Policies of Managing Web Resources at the Canadian Government: A Records Management Perspective - Zwarich, Natasha; Park, Eun G. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
As the importance of Web resources has increased greatly to organizations, this study examines the Web management policies and guidelines of five Canadian government agencies, studies the definitions and characteristics of Web resources from a records management perspective and presents the current policies relevant to the appraisal, retention, and preservation… Comme la quantité des ressources web a fortement augmentée dans les organisations, cette étude examine les politiques de gestion du web et les directives de cinq organismes gouvernementaux canadiens. Elle étudie également les définitions et les caractéristiques des ressources web à partir d’une perspective de gestion des documents et présente les politiques actuelles relatives à l’évaluation, la conservation et la préservation…